Status of the national immunization technical advisory groups in the Americas: recommendations for improvement - Miguel Betancourt-Cravioto; Ruby Trejo Varón; Francisco Becerra-Posada; Carlos Espinal (Pan American Health Organization, 2024)
Objectives. To evaluate the structure and operation of national immunization technical advisory groups (NITAGs) in Latin America and the Caribbean and to make recommendations for improvement. Methods. A convenience sample of six current and eight former NITAG members representing 12 countries in the region were invited in 2022 to answer a web-based questionnaire on NITAG structure, organization, and procedures. The questionnaire used indicators similar to those in the Joint Reporting Form on Immunization. Participants were also asked about the role their NITAGs played in coronavirus disease 2019 (COVID-19) immunization policies. Results. Brazil, Dominican Republic, and Venezuela (Bolivarian Republic of) reported not having an active NITAG. The nine active NITAGs are structured and organized according to World Health Organization and Pan American Health Organization recommendations, with variations between countries. Most NITAGs include representatives of the five recommended medical specialties with the participation of additional members possible. Only Bolivia (Plurinational State of) and Mexico have no explicit policy for managing members' potential conflicts of interest. All NITAGs have an exclusively technical advisory role and generally meet once a quarter. Usually, NITAGs are asked by health ministries to analyze issues and make recommendations. All NITAGs, except for Perus, actively participated in supporting decision-making for immunization policy on COVID-19. Conclusions. NITAGs have successfully supported vaccine policy-making through evidence-based recommendations. However, improvement in their structure, operation, and transparency is needed to help them keep up with the rapidly evolving field of immunization. Research on the impact of NITAGs is important to support the development of recommendations for improvement.